Bevacizumab‐associated intestinal perforation and perioperative complications in patients receiving bevacizumab. Issue 2 (12th February 2020) - Yoshimoto, Toshiaki; Yoshikawa, Kozo; Higashijima, Jun; Miyatani, Tomohiko; Tokunaga, Takuya; Nishi, Masaaki; Takasu, Chie; Kashihara, Hideya; Takehara, Yukako; Shimada, Mitsuo
Abstract: Aim: The purposes of this study are to present cases of emergency surgery in which gastrointestinal perforation occurred during bevacizumab administration, consider the indications for emergency surgery, and examine the safety of scheduled surgery after a washout period for bevacizumab. Methods: (a) We retrospectively investigated seven patients who underwent emergency surgery for bevacizumab‐associated intestinal perforation. (b) We investigated 104 patients with advanced colorectal cancer treated with neoadjuvant therapy who underwent surgery from 2008 to 2018, retrospectively. Results: (a) In the seven patients undergoing emergency surgery for gastrointestinal perforation, the median bevacizumab administration and washout periods were 16 weeks and 24 days, respectively. A stoma was created in all patients except in those who were not candidates. Two patients developed postoperative abdominal abscesses, and two patients died from perioperative sepsis and gastrointestinal bleeding, respectively; both of these patients had poor performance status. (b) In patients receiving bevacizumab (n = 45) and patients treated with bevacizumab‐free regimens as neoadjuvant therapy (n = 59), 31 and 52 patients received chemoradiotherapy, respectively. We found no correlation with postoperative complications with or without bevacizumab. Conclusion: The surgical indications should be considered carefully in patients with gastrointestinal perforation secondary to bevacizumab administration. Meanwhile, after appropriate cessation time, scheduled surgery following bevacizumab administration is feasible. Abstract : In planned surgery, anastomosis after appropriate cessation time of bevacizumab may be acceptable. Surgical indication should be carefully considered in severe perforated cases during bevacizumab administration.